Converting normal computer screens into 3D displays using parallax barriers - Chua, Guo Liang (2014)
In the recent years, 3D movies and games have become more popular due to the rise in demand for 3D content. With the advancement in technology, it is now significantly cheaper to adopt system which support the display of stereoscopic content. Despite so, the cost of setting up stereoscopic system for home use is still relatively expensive. These system would normally require viewers to wear special glasses which might be uncomfortable.